Diseño de una propuesta para la optimización del proceso de abastecimiento en la empresa Gonzalo Rincón e Hijos LTDA (2021)
The main purpose of this degree project is the design of an optimization proposal in the supply process of the company Gonzalo Rincón e Hijos LTDA, starting with the characterization and current diagnosis of the supply processes managed by the company, which in currently it manages an ineffective and outdated system for the proper management of supply processes.